1993
DOI: 10.1126/science.8211118
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Gene Therapy of Hemophilia B: Sustained Partial Correction in Factor IX-Deficient Dogs

Abstract: The liver represents a model organ for gene therapy. A method has been developed for hepatic gene transfer in vivo by the direct infusion of recombinant retroviral vectors into the portal vasculature, which results in the persistent expression of exogenous genes. To determine if these technologies are applicable for the treatment of hemophilia B patients, preclinical efficacy studies were done in a hemophilia B dog model. When the canine factor IX complementary DNA was transduced directly into the hepatocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
175
1
5

Year Published

1994
1994
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(188 citation statements)
references
References 16 publications
7
175
1
5
Order By: Relevance
“…Many different gene delivery methods are available including cationic lipid-based DNA transfection [44][45][46][47][48][49] and retroviral and adenoviral gene transfer vectors; [50][51][52][53][54][55] however, the use of these methods for hepatocytes has not been effective because hepatocytes do not divide, are highly susceptible to toxicity, and transfection efficiencies in hepatocytes are extremely low (HC Isom, unpublished data). 11 Previous studies have reported baculovirus-mediated gene delivery to primary hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Many different gene delivery methods are available including cationic lipid-based DNA transfection [44][45][46][47][48][49] and retroviral and adenoviral gene transfer vectors; [50][51][52][53][54][55] however, the use of these methods for hepatocytes has not been effective because hepatocytes do not divide, are highly susceptible to toxicity, and transfection efficiencies in hepatocytes are extremely low (HC Isom, unpublished data). 11 Previous studies have reported baculovirus-mediated gene delivery to primary hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Although several different viral vectors have been used for the delivery of the FIX gene, vectors to date suffer from either low transduction 7 or exuberant immune response to the vector. 8 Recombinant adeno-associated virus (rAAV) has several features which are suited for FIX gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] In our laboratory, using an in vivo asanguineous model of nonoxygenated perfusion of the regenerating liver, we have demonstrated that rat 24 and dog livers 25 can be transduced after infusion of retroviruses into the portal vein. However, hepatocyte transduction rates were lower than 5% in rats and 1% in dogs.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] In the normal liver, adult hepatocytes are normally quiescent, highly differentiated cells. 19 They are not susceptible to retrovirus transduction that requires active DNA replication for integration into the host cell genome.…”
Section: Introductionmentioning
confidence: 99%